(untitled) (Research, Society and Development, 2024)
Parkinson’s disease (PD) is a neurodegenerative condition affecting millions of elderly people, causing tooth loss and difficulties in oral hygiene. These complications increase the incidence of cavities and periodontal diseases. Oral rehabilitation with dentures is crucial to restore masticatory function and improve the quality of life for these patients. The objective of this study is to evaluate the impact of oral rehabilitation on the quality of life of edentulous older patients with Parkinson’s. An integrative review was prepared following the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), based on the research’s guiding question: "What is the impact of rehabilitation with complete dentures on the quality of life of older patients with Parkinson’s?". The PICO search strategy was set up (P=patient, I=intervention, C=control and O =outcome) and the descriptors that guided the search were obtained from the health sciences descriptors of the virtual health library (DeCSbvs) and the headings of medical subjects (MeSH Pubmed). We used the Pubmed/Medline, BVS, CINAHL, EMBASE, SCOPUS and Web of Science databases, in the last 10 years (between June 2012 and June 2022), presenting title and abstract in English. Used the selection process of the articles occurred according to the three steps of the Prisma Flow Diagram: Step 1: Articles selected through critical and reflective reading by title and summary; Step 2: Articles read in full and included in the review only related to the research theme and Step 3: Selection of articles according to the pre-established inclusion and exclusion criteria. As results, from 42 initial studies were included two studies. Conclusions: there is a lack of studies in the field of quality of life related to dentures in patients with Parkinson disease.